Minimizing Microbial Hazards for Fresh Fruits and Vegetables, Sanitation and Traceback - Gast, Karen L. B.; Holt, Kim (My University, 2000)
This publication describes how to ensure good santitaiton practices and how to effectively track these products.
MF2482_2000_12
Keywords: MF2482; Health and Safety; fruits and vegetables; MF